Images of colonialism and decolonisation in the Italian media - Bertella Farnetti, Paolo; Dau Novelli, Cecilia (Cambridge Scholars Publishing, 2017)
The twentieth century saw a proliferation of media discourses on colonialism and, later, decolonisation. Newspapers, periodicals, films, radio and TV broadcasts contributed to the construction of the image of the African "Other" across the colonial world. In recent years, a growing body of literature has explored the role of these media in many colonial societies. As regards the Italian context, however, although several works have been published about the links between colonial culture and national identity, none have addressed the specific role of the media and their impact on collective mem.